2014
DOI: 10.1111/tri.12450
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome definitions and components in predicting major adverse cardiovascular events after kidney transplantation

Abstract: SummaryMetabolic syndrome (MetS) associates with cardiovascular risk post-kidney transplantation, but its ambiguity impairs understanding of its diagnostic utility relative to components. We compared five MetS definitions and the predictive value of constituent components of significant definitions for major adverse cardiovascular events (MACE) in a cohort of 1182 kidney transplant recipients. MetS definitions were adjusted for noncomponent traditional Framingham risk factors and relevant transplant-related va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Diabetes and hypertension are two of the most frequent chronic diseases in older adults, and also are the most common causes for hospitalization and mortality; this is more evident in populations where high rates of obesity are found, such as the Mexican population. In addition, diabetes is associated with a higher risk of multiple coexisting medical conditions and geriatric syndromes in older persons . In contrast, hypertension is a chronic disease with a slow and silent evolution; persons might not be aware of their condition before a related major event occurs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes and hypertension are two of the most frequent chronic diseases in older adults, and also are the most common causes for hospitalization and mortality; this is more evident in populations where high rates of obesity are found, such as the Mexican population. In addition, diabetes is associated with a higher risk of multiple coexisting medical conditions and geriatric syndromes in older persons . In contrast, hypertension is a chronic disease with a slow and silent evolution; persons might not be aware of their condition before a related major event occurs .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, hypertension is a chronic disease with a slow and silent evolution; persons might not be aware of their condition before a related major event occurs . Both conditions are associated with micro‐ and macrovascular complications, which eventually could lead to dependency, increased need for long‐term care use and death, a similar path to that of frailty.…”
Section: Introductionmentioning
confidence: 99%
“…To optimize outcomes in pediatric liver transplant recipients, attention to chronic medical conditions that impact long‐term morbidity is crucial. PTMS—a clustering of hypertension, dyslipidemia, glucose intolerance, and increased waist circumference that can occur with or without obesity—is increasingly recognized as a significant contributor to long‐term morbidity and mortality after solid‐organ transplantation . In adults after liver transplant, these conditions are associated with long‐term cardiovascular morbidity and mortality …”
Section: Introductionmentioning
confidence: 99%
“…PTMS-a clustering of hypertension, dyslipidemia, glucose intolerance, and increased waist circumference that can occur with or without obesity-is increasingly recognized as a significant contributor to long-term morbidity and mortality after solid-organ transplantation. 1,2 In adults after liver transplant, these conditions are associated with long-term cardiovascular morbidity and mortality. 3,4 We have recently shown that pediatric liver transplant recipients have a higher risk of pre-hypertension and hypertension, impaired glucose tolerance (pre-diabetes), and low HDL than matched peers, even after controlling for obesity and corticosteroid use.…”
Section: Introductionmentioning
confidence: 99%
“…2 In addition, newonset diabetes after transplantation (NODAT), which is a common complication of renal transplantation, is associated with increased rates of long-term complications, including cardiovascular diseases, malignancy, and infections, all of which lead to higher morbidity and mortality rates. 3 Therefore, the long-term outcomes and quality of life of RTRs have started attracting the attention of the research community in recent years.…”
Section: Introductionmentioning
confidence: 99%